2006
DOI: 10.1007/s10295-006-0150-z
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts in an industrial malting ecosystem

Abstract: The malting ecosystem consists of two components: the germinating cereal grains and the complex microbial community. Yeasts and yeast-like fungi are an important part of this ecosystem, but the composition and the effects of this microbial group have been largely unknown. In this study we surveyed the development of yeasts and yeast-like fungi in four industrial scale malting processes. A total of 136 malting process samples were collected and examined for the presence of yeasts growing at 15, 25 and 37 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 61 publications
(111 reference statements)
1
50
0
Order By: Relevance
“…Van Campenhout 58 estimated that approximately 75% of malt xylanase activity was derived from the microbial community and only 25% from the grain. Our recent study 32 showed that the indigenous yeast community may also have a significant impact on the production of cell wall-hydrolysing enzymes. Fungal activity was also involved in the increased proteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Van Campenhout 58 estimated that approximately 75% of malt xylanase activity was derived from the microbial community and only 25% from the grain. Our recent study 32 showed that the indigenous yeast community may also have a significant impact on the production of cell wall-hydrolysing enzymes. Fungal activity was also involved in the increased proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the removal of water during kilning halts both grain and microbial activities. However, kilning has little effect on the viable counts of microbes, which are generally higher in the finished malt than that in the native barley 31,32,46 . The kilning regime has been identified as a significant factor in controlling the microbial community 52 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous study revealed that a numerous and diverse yeast community consisting of both ascomycetous and basidiomycetous species was a signiWcant part of the malting ecosystem [35]. Several yeasts produced plant cell walldegrading enzymes with potentially positive contribution to malt processability.…”
Section: Introductionmentioning
confidence: 99%